2015
DOI: 10.1093/molbev/msv153
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Genetic Diversity in a Wood Decay Mushroom

Abstract: Populations of different species vary in the amounts of genetic diversity they possess. Nucleotide diversity π, the fraction of nucleotides that are different between two randomly chosen genotypes, has been known to range in eukaryotes between 0.0001 in Lynx lynx and 0.16 in Caenorhabditis brenneri. Here, we report the results of a comparative analysis of 24 haploid genotypes (12 from the United States and 12 from European Russia) of a split-gill fungus Schizophyllum commune. The diversity at synonymous sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 33 publications
3
50
0
Order By: Relevance
“…In the American population, where the bias was weaker than expected, one specimen (from Florida) was significantly differentiated from all others (from Michigan, Fig. 1 in [13]). However, excluding this specimen from the analysis only has a minor effect on the bias for this population (not shown), suggesting the discrepancy with our theoretical expectation is not necessarily explained by population structure.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the American population, where the bias was weaker than expected, one specimen (from Florida) was significantly differentiated from all others (from Michigan, Fig. 1 in [13]). However, excluding this specimen from the analysis only has a minor effect on the bias for this population (not shown), suggesting the discrepancy with our theoretical expectation is not necessarily explained by population structure.…”
Section: Discussionmentioning
confidence: 96%
“…To measure the RAD-seq bias in real data, we performed in silico RAD-seq experiments, using full genome sequences from natural populations of Drosophila melanogaster [12] and Schizophyllum commune [13]. For both species, the sequences that are available correspond to haploid genomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the link between the somatic accumulation of mutations during growth and their contribution to the per generation mutation rate, we take advantage of a basidiomycete wood-decay fungus Schizophyllum commune . S. commune is characterized by the highest genetic diversity among all studied species, with nucleotide diversity reaching 20% within a single population (Baranova et al 2015) . The cause of this remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…Together with the published S. commune genome sequence (Ohm et al, 2010) expression of 67 % of the predicted genes was shown as well as a high abundance of antisense transcripts (42 % of the genes). Since then, a comprehensive genome study followed (Baranova et al, 2015) which revealed a high intraspecific diversity. Such high divergence requires that co-isogenic strains be used in transcriptomics and proteomics, as used previously (De Vries et al, 1980;De Vries and Wessels, 1984), or in studies on the metabolome (Menezes et al, 2015), such as the identification of volatile profiles.…”
Section: Introductionmentioning
confidence: 99%